My Stalk Alert: swift response for cyberstalking victims / Wan Rosalili Wan Rosli ... [et al.] - Wan Rosli, Wan Rosalili; Kamaruddin, Saslina; Mohd Saufi, Nadia Nabila; Abd Rani, Ahmad Ridhwan; Husain, Nor Masharah (2021)
In the past two decades, Information and Communication Technology (ICT) has become an integral part of our everyday lives and has intensified with the current endemic, which requires people to work from home. However, such heavy reliance on ICT increased the vulnerability to become the victim of various cyber-crimes, including that of cyberstalking. Cyberstalking has been associated with more severe cyber fraud and real-world crimes such as rape and murder. Due to the nature and severity of such crime, the response by the criminal justice system to cyberstalking remains inadequate within the current Malaysian legal landscape due to the under-reporting and under-responsiveness to such crime. Hence, the MY Stalk Alert (MSA) application was developed and aims at helping and facilitating the victims of stalking specifically and victims of harassment to understand, cope, and provide easily accessible documentation for a compelling trail of evidence within the criminal justice process. Prosecution and investigation of such crimes have been challenging due to the inadequacy of evidence on the victim's part. This Application aims to remedy the circumstances by giving access to users to the features that make it easy to document the evidence and provides them with available information on the crime and the current legal landscape of stalking in Malaysia. Furthermore, the MSA also focused on the user's mental health by providing self-assessment and tips for their wellbeing under the feature of victims' support. The Application is a first of its kind in Malaysia and aims to support victims of stalking in getting the justice they deserve. The findings illustrate that the Application provides the tools needed for victims to report and protect themselves from stalking effectively, which aligns with the assurance of the non-denial of justice for victims as envisaged by the Malaysian Cyber Security Strategy 2020 and the Sustainable Development Goals No.16.